A Tale of Gotong Royong (Mutual Assistance) and Household’s Participations for Communal Activities in Contemporary Indonesia 2012-2014: English - Rusyiana, Aris; Heriyana, Aan (Jurnal Ilmu Komunikasi, 2020)
This paper examines inequality of households’ participation in collective and joint activities Indonesia. And, this paper also investigates the role of people’s collective and joint activities, related to norms-related localism, in cross-provinces study in Indonesia nowadays and in which provinces, people’s collective activities and joint activities are relatively highest among all provinces. Data comes from the National Social Economics Survey 2012 and 2014 and Village Potential Census (Podes) in 2011 and 2014 which consists of household participations’ as collective activity and the information of how many villages mostly prone to natural disasters. Drawing Podes 2011 and Podes 2014, these preliminary finding indicates that Indonesia still has varied density of localism cross-provinces in this contemporary communication sciences issue and globalization era. The specific terms of localism promote collective activity which includes mutual assistance (gotong royong). Descriptive statistical records mutual assistance (Gotong Royong) increases in Indonesia in 2014 (90.93 %) among villages cross-provinces from (88.80%) villages that still held it in 2011. Likewise, results from SUSENAS’s descriptive statistics also shows that communal activities in helping people from natural disasters are varied among provinces, as well as in public interest, religious activities and social activities. In another case, results of Pearson Bivariate Correlation show that the natural disasters occurrence associate with the percentage of households which often and always participate in helping natural disaster victims. These preliminary findings indicate the improved phenomena of density of kindness in order to communicate empathy among people, especially during existence of natural disasters. Despites unsignificant intercorrelation between two variables (density of communal services and occurrence of natural disasters), these preliminary findings indicate strengths of the value of mutual aid/mutual assistance/gotong royong in the contemporary of Indonesia. Although the finding shows no significant association between post natural disasters and density of communal activities, these preliminary findings indicate that communal activities may associate with the kindness among people in order to show their mutual self-help in all conditions, not only when natural disasters strikes cross-Indonesian provinces.